The optical E-band use in the NG-RAN/O-RAN radio signals transmission over ODN path - Zakrzewski, Zbigniew (Photonics Letters of Poland, 2023)
The paper presents results of the analysis of the occupancy of optical bands in the ODN by systems from the xPON family. The analysis results show that the free NG Option 2 range, located in the optical E-band, can be successfully used to transport the NG-RAN/O-RAN radio signals over the ODN path. Calculations showing the maximum range of optical fronthaul links for CPRI/eCPRI interfaces were performed. Analyzes supported by calculations and computer simulations were performed, which show the possibility of using optical E-band to transport the A-RoF (RFoF) radio signals over ODN using high radio frequencies approved by 3GPP for use in the NR interface of 5G Rel-17 mobile systems. Full Text: PDF References ITU-T G.652 (2016), DirectLink ITU-T G.657 (2016). DirectLink ITU-T G.984.5 (2022). DirectLink S. Okamoto, K. Minoguchi, F. Hamaoka, K. Horikoshi, A. Matsushita, M. Nakamura, E. Yamazaki, and Y. Kisaka, "A Study on the Effect of Ultra-Wide Band WDM on Optical Transmission Systems", J. Light. Technol., 38, 5 (2020). CrossRef N. Sambo, B. Correia, A. Napoli, J. Pedro, L. Kiani, P. Castoldi, and V. Curri, "Network upgrade exploiting multi band: S- or E-band?", J. Opt. Commun., 14, 9 (2022). CrossRef C. Zhang, X. Liu, J. Li, A. Zhang, H. Liu, L. Feng, K. Lv, S. Liao, Z. Chang, and J. Zhang, "Optical Layer Impairments and Their Mitigation in C+L+S+E+O Multi-Band Optical Networks With G.652 and Loss-Minimized G.654 Fibers", J. Light. Technol., 40, 11 (2022). CrossRef ITU-T G.9805 (2022). DirectLink Z. Zakrzewski, "Optical RRH working in an all-optical fronthaul network", Proc. SPIE, 10603: 1-12 (2017). CrossRef Z. Zakrzewski, "D-RoF and A-RoF Interfaces in an All-Optical Fronthaul of 5G Mobile Systems", Appl. Sci. 10, 1212 (2020). CrossRef ITU-T G.Sup39 (2016). CrossRef G.P. Agrawal, Fiber-Optic Communication Systems, 5th Edition, (New York, John Wiley & Sons, Inc 2021). CrossRef C. Lim, A. Nirmalathas, M. Bakaul, K-L. Lee, D. Novak, and R. Waterhouse, "Mitigation strategy for transmission impairments in millimeter-wave radio-over-fiber networks [Invited]", J. Opt. Netw. 8, 2 (2009). CrossRef Z. Zakrzewski, "Optical Channel Selection Avoiding DIPP in DSB-RFoF Fronthaul Interface", Entropy, 23(11), 1554 (2021). CrossRef